HUBUNGAN ANTARA POLA KONSUMSI DAN AKTIVITAS FISIK DENGAN STATUS GIZI PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA UNIT ABIYOSO YOGYAKARTA - Ismayanti, Nurika; Solikhah, . (Universitas Ahmad Dahlan, 2012)
Background: Elderly Group is included into nutritional susceptible group because of specific feature causing this group easily affected by malnutrition. Age increasing in someone causes a low metabolism velocity. It can be solved by giving nutritional need adequate for elderly. Thus, paying attention to con-sumption pattern is an important thing to keep their nutritional status. Aside from giving a good nutrition, physical activity is also a thing that should be paid attention to in elderly. The aims of this research are for consumption pattern, physical activity, nutritional status, and relation between consumption pattern and physical activity with nutritional status in elderly in Panti Sosial Trena Werdha (PTSW) Unit Abiyoso Yogyakarta, at year 2011. Methods: Cross sectional was chosen as the design of this research. Population in this research was all elderly in PTSW Unit Abiyoso Yogyakarta. Sample taken in this research was population that filled inclu-sion criteria established by the researcher, so that sample obtained 53 people. Instrument research used was direct measure and questionnaire interview, and analyze used was Chi square. Results: Based on bi-variety test, there is no significant relation between consumption pattern and nutri-tional status, seen from RP=0,811 with Confident Interval 0,479<RP<1,372. And there is no significant relation between physical activity and nutritional status, seen from RP= 1,005 with Confident Interval 0,638<RP<1,585. Conclusion: There is no significant relation between consumption patterns and physical activity with nutritional status in elderly in Panti Sosial Tresna Werdha (PSTW) Unit Abiyoso Yogyakarta, at year 2011. Keywords: consumption patterns, physical activity, nutritional status